Optimized structure of asymmetric polybenzimidazole membranes to improve anion exchange membrane water electrolysis performance - Lee, Ju Yeon; Choi, Young Bin; Lee, Hye Jin; Lim, Katie Heeyum; Park, Hee-Young; Jang, Jong Hyun; Lee, So Young (Elsevier, 2025)
We developed an asymmetric polybenzimidazole (Asy-PBI) membrane for alkaline electrolysis of water (AEMWE). This membrane features a unique design comprising both a porous layer and a thin dense layer, which together enhance overall performance. The porous layer of Asy-PBI enhances ionic conductivity while contributing to mechanical stability by increasing the absorption of water and KOH. In contrast, the thin dense layer reduces mass transfer resistance, further boosting the efficiency of the membrane. Comparative measurements indicated that Asy-PBI exhibited improved properties than those of the conventional dense polybenzimidazole membrane (Dense-PBI), achieving a KOH absorption rate of 201 % and a hydroxide conductivity of 84.3 mS cm-1 AEMWE single-cell performance demonstrated that Asy-PBI exhibits about six times higher current density than that of Dense-PBI (3.45 A cm-2 vs. 0.56 A cm-2) at a cell voltage of 2.0 V in 20 wt% KOH solution at 80 degrees C. Furthermore, in the AEMWE long-term stability test, Asy-PBI maintained a current density of 500 mA cm-2 for over150 h at 80 degrees C. Overall, this study could demonstrate that the asymmetric membrane structure is advantageous over the conventional dense structure for AEMWE applications.